Transcriptome analysis of Vibrio parahaemolyticus in type III secretion system 1 inducing conditions - Seth David Nydam; Seth David Nydam; Devendra H. Shah; Devendra H. Shah; Douglas Ruben Call; Douglas Ruben Call (Frontiers in Cellular and Infection Microbiology, 2014)
Vibrio parahaemolyticus is an emerging bacterial pathogen capable of causing inflammatory gastroenteritis, wound infections and septicemia. As a food-borne illness, infection is most frequently associated with the consumption of raw or undercooked seafood, particularly shellfish. It is the primary cause of Vibrio-associated food-borne illness in the United States and the leading cause of food-borne illness in Japan. The larger of its two chromosomes harbors a set of genes encoding type III section system 1 (T3SS1), a virulence factor present in all V. parahaemolyticus strains that is similar to the Yersinia ysc T3SS. T3SS1 translocates effector proteins into eukaryotic cells where they induce changes to cellular physiology and modulate host-pathogen interactions. T3SS1 is also responsible for cytotoxicity towards several different cultured cell lines as well as mortality in a mouse model. Herein we used RNA-seq to obtain global transcriptome patterns of V. parahaemolyticus under conditions that either induce (growth in DMEM media, in trans expression of transcriptional regulator exsA) or repress T3SS1 expression (growth in LB-S media, in trans exsD expression) and during infection of HeLa cells over time. Comparative transcriptomic analysis demonstrated notable differences in the expression patterns under inducing conditions and was also used to generate an expression profile of V. parahaemolyticus during infection of HeLa cells. In addition, we identified several new genes that are associated with T3SS1 expression and may warrant further study.